2006
DOI: 10.1111/j.1475-4932.2006.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Firm Size and the Use of Intellectual Property Rights*

Abstract: Innovation markets are often characterised by market failure because inventions typically incur high fixed costs relative to marginal costs and their intellectual capital is non‐excludable. Intellectual property (IP) rights may attenuate this problem by providing legal recourse for firms to stop imitation by rivals. As IP rights are costly to acquire and enforce, it is often argued that SMEs are disadvantaged in their ability to utilise IP rights. This paper examines the intensity of IP usage by firm size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
2
45
0
1
Order By: Relevance
“…This can create disadvantages to SMEs when compared with big enterprises in the development of skills for the use of intellectual property rights which produce a low level of innovation in SMEs (Cordes et al, 1999;WIPO, 2003;Macdonald, 2004;Jensen & Webster, 2006). The investigation of Arundel and Kabla (1998) provides empirical evidence by showing that SMEs from Europa have a low tendency to patent their innovations in comparison to big enterprises.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This can create disadvantages to SMEs when compared with big enterprises in the development of skills for the use of intellectual property rights which produce a low level of innovation in SMEs (Cordes et al, 1999;WIPO, 2003;Macdonald, 2004;Jensen & Webster, 2006). The investigation of Arundel and Kabla (1998) provides empirical evidence by showing that SMEs from Europa have a low tendency to patent their innovations in comparison to big enterprises.…”
Section: Introductionmentioning
confidence: 95%
“…The investigation of Arundel and Kabla (1998) provides empirical evidence by showing that SMEs from Europa have a low tendency to patent their innovations in comparison to big enterprises. In a more recent study, Jensen and Webster (2006) proved that SMEs from Australia have lower patent registrations, trademarks and industrial designs than big enterprises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…À ce titre, nous confirmons donc que les petites entreprises brevètent prioritairement les innovations qui ont une valeur de marché suffisante pour envisager un dépôt dans plus de 10 pays différents (Obayashi et Yamada, 2009). Enfin, les données du LES confirment que le recours aux licences est en moyenne plus important au sein des grandes entreprises (et ce quel que soit le type d'accord considéré), compte tenu de leur plus grande propension à breveter (Jensen et Webster, 2006). …”
Section: Tableau 3 Taille Des Entreprises Et Internationalisation Deunclassified
“…Lakdawalla and Sood (2009) discussed the characteristics of the electronics, biology, pharmaceutical, telecommunications and manufacturing industries, as well as the differences in innovation capabilities of those industries (Lakdawalla, Sood 2009;Cooke 2002;Tseng, Wu 2007). Jensen and Webster (2006) used patent data to study the relationship between firm size and patent intensities in Australia. Bessen andMaskin (2009) andGeradin et al (2011) found that the number of patents is highly correlated with firm size, and larger companies tend to treat patents as a competitive niche (Kim et al 2008;Blind et al 2009;Trippl, Maier 2010).…”
Section: Literature Reviewmentioning
confidence: 99%